2015 2nd International Conference on Electronics and Communication Systems (ICECS) 2015
DOI: 10.1109/ecs.2015.7124952
|View full text |Cite
|
Sign up to set email alerts
|

Efficient anomaly detection and mitigation in software defined networking environment

Abstract: A Computer network or data communication network is a telecommunication network that allows computers to exchange data. Computer networks are typically built from a large number of network devices such as routers, switches and numerous types of middle boxes with many complex protocols implemented on them. They need to accomplish very complex tasks with access to very limited tools. As a result, network management and performance tuning is quite challenging. Software-Defined Networking (SDN) is an emerging arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…A large variety of meta-heuristic algorithms such as ACO [183][184][185][186][187][188][189][190][191], EAs [192][193][194], GAs [195][196][197][198][199][200][201][202][203], PSO [204][205][206][207][208][209], SA [210][211][212], bee colony optimisation-based [213,214], whale optimisation [215,216], FFO [217], BA [85], TLBO [87] and GWO [207] were used in SDN.…”
Section: Meta-heuristic Algorithms Used In Sdnmentioning
confidence: 99%
See 2 more Smart Citations
“…A large variety of meta-heuristic algorithms such as ACO [183][184][185][186][187][188][189][190][191], EAs [192][193][194], GAs [195][196][197][198][199][200][201][202][203], PSO [204][205][206][207][208][209], SA [210][211][212], bee colony optimisation-based [213,214], whale optimisation [215,216], FFO [217], BA [85], TLBO [87] and GWO [207] were used in SDN.…”
Section: Meta-heuristic Algorithms Used In Sdnmentioning
confidence: 99%
“…The experimental results showed that FFA produced efficient and accurate results. [85] employed BBA for feature selection in an SDN-based intrusion detection system. Based on the experiments conducted on NSL-KDD dataset, the selected features achieved a detection rate of 90.9, 91.1, 80.2 and 98.1% for DoS, Probe, R2L and U2R attack types, respectively, with low false positive rates when used with J48 DT.…”
Section: Ffo In Sdnmentioning
confidence: 99%
See 1 more Smart Citation
“…It performs C4.5 algorithm to build the decision tree for classifying the traffic. The proposed work in [17] focuses on identifying network anomalies efficiently under SDN environment using bat algorithm metaheuristic method for feature extraction and entropy-based decision tree for traffic classification. In [18], Kim et al propose a three-layer recurrent neural network (NN) acting as a neural classifier for misuse detection.…”
Section: Related Workmentioning
confidence: 99%
“…Sathya's proposed work aims to detect the attacks on SDN environment by using a heuristic algorithm inspired by the echolocation behavior of bats. Detecting anomalies in SDN environment will be more manageable and efficient [15].…”
Section: Related Workmentioning
confidence: 99%